Electrophoretic separation and deposition of metal–graphene nanocomposites and their application as electrodes in solar cells. Issue 68 (5th July 2016) - Brennan, Lorcan J.; Surolia, Praveen K.; Rovelli, Lorenzo; Loudon, Alexander; Torsney, Samuel P.; Roche, Sarah; Thampi, K. Ravindranathan; Gun'ko, Yurii K.
Abstract : Synthesis of metal nanoparticle–graphene composites without the use of any stabilising ligands has enabled the nanoparticle surface to be available for electron transfer reactions in the development of new counter electrodes for solar cells. Abstract : Graphene oxide (GO) is a 2D material which offers great promise in many applications, owing primarily to the reactive surface which enables an easy surface functionalization and solution processing of the resulting materials. Herein we demonstrate that graphene oxide (GO) can be used as a supporting template for the production of new graphene–metal nanoparticle composites. Our synthetic strategy allowed for nanoparticle deposition (Pt and Au) onto the surface of the 2 dimensional carbon nano-substrate without stabilising ligands. Moreover we have shown that the composite materials can be further processed using electrophoretic deposition (EPD). The deposition of the materials onto conducting glass substrates (namely fluorine doped tin oxide) via EPD, allows for the formation of high quality, stable electrodes. These electrodes demonstrated a tuneable electrochemical response towards the reduction of the tri-iodide ion, when studied electrochemically. These electrodes were then tested as potential counter electrodes (CEs) in dye sensitized solar cells (DSSCs) and displayed very promising results, increasing the efficiency by 47.5%, when compared to a conventional Pt electrode.